(untitled) (Revista Internacional de Folkcomunicação, 2024)
Holy Week celebrations in Brazil begin on Palm Sunday and end with Easter Sunday, remembering the crucifixion, death and resurrection of Jesus Christ. During this period, the Judas workout takes place, where a doll symbolizing Judas Iscariot is punished by the community. This article, from the perspective of Folkcommunication, investigates the origins and redefinition of this practice, analyzing digital journalism news from the North and Northeast of Brazil. The exploratory research uses bibliographic and documentary methods, in addition to the analysis of journalistic articles from 2024 from the portals O Povo (CE), O Liberal (PA) and Folha BV (RR).